1984
DOI: 10.1136/oem.41.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain in rubber chemical workers exposed to carbon disulphide and methaemoglobin formers.

Abstract: A cross sectional prevalence study of chest pain in 94 rubber chemical workers exposed to carbon disulphide (CS2) and methaemoglobin forming aromatic amines was carried out. The purpose of the study was to determine whether the prevalence of chest pain or coronary heart disease (CHD), or both, in exposed individuals exceeded that of a group of non-exposed individuals from the same plant. Cardiovascular, smoking, and occupational histories were obtained. Blood pressure, height, weight, serum cholesterol, and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The relationship between carbon disulfide and IHD has been confirmed during the 1980s in American studies (255,256), of which the latest (256) is the largest ever undertaken, the cohort studied comprising more than 10 000 workers .…”
Section: Carbon Disulfidementioning
confidence: 93%
“…The relationship between carbon disulfide and IHD has been confirmed during the 1980s in American studies (255,256), of which the latest (256) is the largest ever undertaken, the cohort studied comprising more than 10 000 workers .…”
Section: Carbon Disulfidementioning
confidence: 93%
“…The studies by Franco et al, Oliver and Weber,Stanosz et al and Sugimoto et al [10,38,47,50,51] were problematic for several reasons. None of these assessed or controlled for confounding by cardiac risk factors other than age and gender, and limited analyses of exposure precluded the assessment of the effect of duration or presence of a dose-response relationship.…”
Section: Chd Risk Indicators and Low Exposure Conclusionmentioning
confidence: 96%
“…Four used matching in the construction of the study populations, but reported unmatched analyses with no explanation [4,9,10,51]. Three reported low and differential participation rates for the exposed and unexposed cohorts [1,8,43], and one reported analyses of rubber industry employees who experienced very low levels of exposure to CS 2 in addition to a number of additional, potentially cardiotoxic exposures that were unlikely to be adequately controlled for in the analysis [38]. Although these papers were inadequate for inclusion in a quantitative assessment of the effect of low-level exposure to CS 2 , their results were influential in our overall conclusions, and are therefore summarized in the text that follows.…”
Section: Cardiac Risk Indicators and Low Exposures To Carbon Disulfidementioning
confidence: 96%
See 1 more Smart Citation
“…The existence of an intervention program with evaluation of cardiac risk factors from 1975 on would appear to make the ®ndings of Oliver and Weber (1984) of increased chest pain and possible/de®nite IHD among workers in the rubber chemicals department examined in 1980, and our ®nding of increased IHD mortality in the 1980±1994 time period, of even greater concern.``H owever well intended the authors' recommendations, they are not well supported by the results of the study.' ' We continue to believe that the presentation of results was well balanced in this paper and that the recommendations are reasonable.…”
mentioning
confidence: 94%